Comparative karyotype and RAPD analysis for characterizing three varieties of Lycopersicon esculentum Mill. (Bangladesh Journal of Botany, 2013)
Three tomato varieties (Lycopersicon esculentum Mill.) viz. BARI tomato-11, BARI tomato-2 and BARI tomato-3 released from Bangladesh Agriculture Research Institute (BARI) were characterized by karyotype analysis and RAPD markers. BARI tomato-11 and BARI tomato-2 were found to possess 2n = 24 metacentric chromosomes. On the other hand, 2n = 25 metacentric chromosomes were observed in BARI tomato-3 revealing a trisomic variety. The karyotype of the three varieties was very symmetric and each of the varieties showed specific and unique RAPD fingerprinting. Therefore, based on karyotype and RAPD analysis the three tomato varieties could be characterized. DOI: http://dx.doi.org/10.3329/bjb.v41i2.13439 Bangladesh J. Bot. 41(2): 149-154, 2012 (December)